THE EFFECT OF STREPTOMYCIN ON SOME MORPHOLOGICAL PARAMETERS OF THREE ACCESSIONS OF BAMBARA NUT (Vigna subterrenea (L) Verde) (FUDMA JOURNAL OF SCIENCES, 2020)
Bambara nut (Vigna subterrenea (L) Verde) is a major source of vegetable protein in sub - Saharan Africa. It is well adapted to harsher conditions and constitutes an important part of the local diet, culture and economy. The effects of streptomycin on some morphological parameters of three accessions of Bambara nuts was investigated in this study. Three healthy and viable bambara nut (Vigna subterranean) accessions were collected from IITA, Ibadan, Nigeria. They include: TVSU-1, TVSU-9 AND TVSU-10. Streptomycin was obtained from a reputable pharmaceutical store located along Abuja Road, Lafia, Nasarawa state. Garden soil was collected from the research garden and filled into polyethene pots after which they were perforated at the bottom. Randomized Complete Block Design (RCBD) was adopted with each treatment consisting of 3 replicates. Polyethylene bags were properly labeled according to a given treatment name and replicate number. Five (5) different concentrations of Bambara Nut were measured with the aid of weigh balance. This concentration is; 0.1g/L, 0.2g/L, 0.3g/L, 0.4g/L and lastly 0.5g/L. Different   Accessions of Bambara Nut were primed into this different concentration. From the results obtained, the number of leave was highest at the lowest concentration in TVSU-1. In TVSU-9 0.3g/L had the highest number of leaves. However, control had the highest number of leaves in TVSU-10. In Plant height, the lower concentration had more plant height compared to other treatments.
Keywords: Streptomycin, accessions, Bambara nuts, yield